A Synthesis and Meta-Analysis of Reading Interventions Using Social Studies Content for Students With Learning Disabilities. (March 2014) - Swanson, Elizabeth; Hairrell, Angela; Kent, Shawn; Ciullo, Stephen; Wanzek, Jeanne A.; Vaughn, Sharon
A synthesis and meta-analysis of the extant research on the effects of reading interventions delivered using social studies content for students with learning disabilities in kindergarten through Grade 12 is provided. A total of 27 studies met criteria for the synthesis, with 16 studies providing sufficient data for inclusion in the meta-analysis. Reading interventions implemented within the context of social studies have employed the use of graphic organizers, mnemonics, reading and answering questions, guided notes, and multicomponent comprehension instruction. The overall mean effect size for interventions included in the meta-analysis was 1.02, indicating that reading interventions delivered using social studies content have a substantial positive effect on outcomes among students with learning disabilities.